1992
DOI: 10.1093/jaoac/75.6.1124
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching of Methylene Blue as an Index of Lipoxygenase Activity

Abstract: An assay of lipoxygenase activity was developed that depends on measurements of the time needed for the bleaching of methylene blue to begin. This time was inversely related to the level of lipoxygenase activity (y = 114.5132 - 0.0132x; r= -0.99); it was not affected by the concentration of methylene blue, linoleic acid, or hydroperoxide. Lipoxygenase activity can be calculated from the time needed for the bleaching of methylene blue to begin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…These results indicated that test I could selectively detect the L-l isozyme contained in soybean extracts. Toyosaki (1992) proposed that methylene blue bleaching occurred as a result of the sequence of production of the lipid radical R" and the peroxy radical ROO*. Another simple explanation is that a redox reaction is likely involved in this bleaching reaction, because methylene blue is known to be a redox indicator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that test I could selectively detect the L-l isozyme contained in soybean extracts. Toyosaki (1992) proposed that methylene blue bleaching occurred as a result of the sequence of production of the lipid radical R" and the peroxy radical ROO*. Another simple explanation is that a redox reaction is likely involved in this bleaching reaction, because methylene blue is known to be a redox indicator.…”
Section: Resultsmentioning
confidence: 99%
“…There are some studies dealing with dye solution bleaching by soybean lipoxygenases. Toyosaki (1992) showed that commercial L-l bleached methylene blue, although it was uncertain whether other isozymes did so. Kikuchi and Kitamura (1987) reported three tests and two versions for the detection of lipoxygenase isozymes by skillful use of the different action among the carotene bleaching activities of three lipoxygenase isozymes; however, the tests involved complex procedures and careful handling for the detection of the L-l or L-2 isozyme in soybean seeds lacking the L-3 isozyme.…”
Section: Introductionmentioning
confidence: 99%
“…Several such methods exist. An assay based on the bleaching (reduction) of methylene blue was developed by Toyosaki (7). This method, although simple and rapid, is not particularly sensitive and is difficult to quantify.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fluorescein for detection of soybean LOX-1 was modeled using the previous methylene blue bleaching method (7). The methylene blue LOX assay measures the bleaching of methylene blue by hydroperoxides formed by the radical-mediated enzymatic oxidation of linoleic acid (15). The new fluorescein assay measures the decrease in fluorescence of fluorescein as it is degraded by hydroperoxide radical attacks.…”
Section: Development Of Lox-1 Assay Using Fluorescein As the Probementioning
confidence: 99%
“…There are other methods that quantify LOX activity. For example, the methylene blue assay quantifies the enzyme by measuring time until bleaching begins (15). Measuring the AUC of fluorescence allows for more objective and accurate quantification.…”
Section: Development Of Lox-1 Assay Using Fluorescein As the Probementioning
confidence: 99%